Photovoltaic-Thermal Side-Absorption Concentrated Module with Micro-Structures as Spectrum-Division Component for a Hybrid-Collecting Reflection Solar System - Jyh-Rou Sze; An-Chi Wei (Energies)
A photovoltaic-thermal side-absorption concentrated module (PT-SACM) based on spectrum division for photovoltaic-thermal hybrid applications is carried out. In order to reduce the absorption by materials and the axial-chromatic aberration caused by the transmissive optical system and to improve the performance of the entire system, a reflective system, the parabolic mirror array, fabricated by the ultra-precision diamond turning technology, is proposed herein. For the purposes of spectrum division, thinner volume, lightweight, and wide acceptance angle, the proposed module is designed with a diffraction optical element (DOE), a light-guide plate with a micro-structure array and a parabolic mirror array. Among them, the DOE can separate the solar spectrum into the visible band, which is converted to electrical energy via photovoltaics, and the infrared band, whose thermal energy is collected. Experimental measurements show that the overall optical efficiency of the entire system reached 38.32%, while a deviation percentage of 3.5% is calculated based on the simulation. The system has successfully demonstrated the separation of visible and infrared bands of the solar spectrum. Meanwhile, the lateral displacement between the micro-structures of the light-guide plate and the focus of the parabolic mirror array can be used to compensate for the angular deviation of the sun incidence, thereby achieving wide-angle acceptance via the proposed solar concentration system.